Effects of gamifying questions on English grammar learning mediated by epistemic curiosity and language anxiety. Issue 7 (3rd September 2022) - Hong, Jon-Chao; Hwang, Ming-Yueh; Liu, Yi-Hsuan; Tai, Kai-Hsin
Abstract: Different types of gamification can be advantageous to enhancing students' learning. In contrast to the extant gamification literature focusing on designing reward systems and/or facilitating teachers' gamification of learning contents, this study focuses on the gamifying of learning content by students. To verify the efficacy of gamification as a learning activity, the effects of students posing and gamifying questions in relation to second language grammar learning are explored. A gamification platform called TipOn was designed to allow students to pose and gamify questions according to different game modes to facilitate their classmates' practicing English grammar. To examine the emotional regulation effects of posing and gamifying questions on learning performance, this study explored the effectiveness of gamifying content by examining how participants' two types of epistemic curiosity (i.e., interest-type epistemic curiosity (IEC) and deprivation-type epistemic curiosity (DEC)) related to posing questions affected their attitude towards gamification (ATG) and their learning progress. In this experiment, participants had to pose English grammar questions related to verb tense, and gamify the questions using TipOn. They then played games using other students' content. Data were collected from 96 ninth-grade students, and the correlations between constructs were evaluated using the path-analytical technique. The research results indicated that, first, English learning anxiety is negatively related to the two aforementioned types of epistemic curiosity. Second, IEC had no significant impact on ATG; however, DEC was positively associated with ATG. Third, ATG could positively predict students' learning progress. The results imply that teachers could use this gamifying system in a flipped classroom to motivate students to tap into their epistemic curiosity to increase their content learning and enhance the effects of learning.